The Protective Effect of Heme Oxygenase-1 against Intestinal Barrier Dysfunction in Cholestatic Liver Injury Is Associated with NF-κB Inhibition - Lijing Zhang; Zhenling Zhang; Bojia Liu; Yanling Jin; Yan Tian; Yi Xin; Zhijun Duan (BMC, 2017)
Abstract Heme oxygenase-1 (HO-1) is reported to protect against liver injury, but little Is known about its effect on the intestinal barrier in cholestatic liver injury. In this study, we investigated the effects of HO-1 and its enzymatic by-product on intestinal barrier dysfunction in bile duct ligation (BDL) rats and explored the possible mechanism. The HO-1 inducer cobalt protoporphyrin (CoPP) and carbon monoxide-releasing molecule-2 (CORM-2) were used; the expression levels of tight junction (TJ) proteins, intestinal inflammation and NF-κB p65 were measured. For an in vitro experiment, stable Caco-2 cell lines were constructed, one overexpressed the HO-1 gene and another with that gene knocked down, and the specific NF-κB inhibitor JSH-23 was used. CoPP and CORM-2 treatment alleviated liver and intestinal mucosa injury in BDL rats; improved ZO-1, claudin-1 and PCNA expression; and reduced cell apoptosis and intestinal interleukin-6 (IL-6) expression. In vitro studies confirmed that HO-1, ZO-1 and occludin were overex-pressed in HO-1-transfected Caco-2 cells, while decreased in the short hairpin HO (sh-HO-1) group. JSH-23 significantly increased occludin expression in both the HO-1 overexpression and sh-HO-1 groups, compared with their respective controls. HO-1 overexpression also inhibited the nuclear translocation of NF-κB p65 after lipopolysaccharide (LPS) treatment. Additionally, phospho-p65 expression in sh-HO-1 cells was significantly increased compared with that of the HO-1 overexpression group. In conclusion, HO-1 and CORM-2 improved intestinal epithelial barrier function in BDL-induced cholestatic liver injury mainly by restoring TJ, reducing cell apoptosis and intestinal inflammation. HO-1 exerts a protective effect, which is partially correlated with the regulation of NF-κB.